2005
DOI: 10.1016/j.femsle.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of theStaphylococcus aureus tstgene among community- and hospital-acquired strains and isolates from Wegener's Granulomatosis patients

Abstract: To allow rapid identification of toxic shock syndrome toxin-1 (TSST-1)-producing Staphylococcus aureus strains, a real-time PCR assay for the detection of the tst gene, which encodes TSST-1, was developed. The assay was applied to S. aureus isolates from patients with Wegener's Granulomatosis (WG), as well as isolates that were classified as either community- (CA) or hospital-acquired (HA). No significant difference in the percentage of tst-positive strains was observed between isolates from WG patients and CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…In this research, 40 strains were isolated from sick children, 10 strains from nurses' hands and 5 strains from the equipment [20] Another research was done in 2005; in this research 103 strains of Staphylococcus aureus were isolated from community, hospital and patients with granulomatous. 12 strains out of 51 strains isolated from community, 5 strains out of 34 strains isolated from hospital and 4 strains out of 16 strains isolated from patients with granulomatous reported presence of tst gene [21]In the present research, 29 strains out of 35 strains isolated from the patients, 5 strains out of 6strains isolated from the personnel and 15 strains out of 20 strains isolated from the equipment included tst gene. Moreover, 16 strains out of 35 strains isolated from the patients, 4 strains out of 6 strains isolated from the personnel and 8 strains out of 20 strains isolated from the equipment included eta gene.…”
Section: Resultssupporting
confidence: 44%
“…In this research, 40 strains were isolated from sick children, 10 strains from nurses' hands and 5 strains from the equipment [20] Another research was done in 2005; in this research 103 strains of Staphylococcus aureus were isolated from community, hospital and patients with granulomatous. 12 strains out of 51 strains isolated from community, 5 strains out of 34 strains isolated from hospital and 4 strains out of 16 strains isolated from patients with granulomatous reported presence of tst gene [21]In the present research, 29 strains out of 35 strains isolated from the patients, 5 strains out of 6strains isolated from the personnel and 15 strains out of 20 strains isolated from the equipment included tst gene. Moreover, 16 strains out of 35 strains isolated from the patients, 4 strains out of 6 strains isolated from the personnel and 8 strains out of 20 strains isolated from the equipment included eta gene.…”
Section: Resultssupporting
confidence: 44%
“…In this study, agr IV was not found in any isolates, similar to what was observed in a previous report 29 , suggesting that the agr IV S. aureus isolate was not common. The agr III and IV groups were associated with tst and exfoliatin toxin production, respectively 30,31 . The tst gene was most common in the agr II S. aureus isolates (59%), followed by the agr III (27%) and agr I (14%) isolates.…”
Section: Discussionmentioning
confidence: 99%
“…de). To confi rm the association between MLST and spa typing, in combination with BURP, MLST was performed on a representative set of 12 strains of each major spa type and spa-CC (2).The presence of CNA, PVL, and TSST-1 was determined with real-time PCR assays (14,15).…”
Section: Typing Methodsmentioning
confidence: 99%